Highly Conductive Films by Rapid Photonic Annealing of Inkjet Printable Starch–Graphene Ink. Issue 5 (30th December 2021) - Majee, Subimal; Zhao, Wei; Sugunan, Abhilash; Gillgren, Thomas; Larsson, Johan A.; Brooke, Robert; Nordgren, Niklas; Zhang, Zhi‐Bin; Zhang, Shi‐Li; Nilsson, David; Ahniyaz, Anwar
Abstract: A general formulation engineering method is adopted in this study to produce a highly concentrated (≈3 mg mL −1 ) inkjet printable starch–graphene ink in aqueous media. Photonic annealing of the starch–graphene ink is validated for rapid post‐processing of printed films. The experimental results demonstrate the role of starch as dispersing agent for graphene in water and photonic pulse energy in enhancing the electrical properties of the printed graphene patterns, thus leading to an electrical conductivity of ≈2.4 × 10 4 S m −1 . The curing mechanism is discussed based on systematic material studies. The eco‐friendly and cost‐efficient approach presented in this work is of technical potential for the scalable production and integration of conductive graphene inks for widespread applications in printed and flexible electronics. Abstract : A water‐based inkjet printable graphene ink is formulated using starch nanoparticles as dispersing agent, thus eliminating conventional harmful solvents and additives. Rapid photothermal post‐treatment of the printed patterns is demonstrated without damaging the underneath substrate. The resulting starch–graphene films shows high electrical conductivity of 2.4 × 10 4 S m −1, on par with the highest values reported in the literature.